Anomalous Origin and Retropulmonary Course of an Atherosclerotic Stenosed Left Circumflex Coronary Artery - J. A. T. C. Parker; A. A. Peivandi; S. Bitschnau; N. Kayhan; C. F. Vahl (International Journal of Vascular Medicine)
We here present the case of a rarely seen anomalous origin and retropulmonary course of the left circumflex artery from the proximal right coronary artery. The patient suffered from coronary ischemia due to stenotic lesions both in the aberrant circumflex coronary artery and in the first and second diagonal branches. Coronary bypass operation was performed.